2020
DOI: 10.1039/c9bm01247h
|View full text |Cite
|
Sign up to set email alerts
|

Meta-biomaterials

Abstract: Meta-biomaterials are designer biomaterials with unusual and even unprecedented properties that primarily originate from their geometrical designs at different (usually smaller) length scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 156 publications
1
62
0
3
Order By: Relevance
“…[15] AM techniques enable the production of geometrically complex, multimaterial medical implants with spatially heterogeneous properties that would otherwise be challenging to produce by traditional techniques. [16][17][18][19] A major AM technique utilized is extrusion-based processes to produce filaments due to the versatility and simplicity of the technique which enables a variety of materials to be processed, the ability to print in a cell-friendly Additive Manufacturing 3D printing techniques are utilized to produce biomaterial scaffolds with porous architectures that enable cell attachment, biological factors, and appropriate mechanical strength. As the basic building block of a scaffold, the individual filaments should have sufficient mechanical properties, comprising high compressive loading, and fracture resistance to mimic the natural tissue organisation.…”
Section: Doi: 101002/mame201800173mentioning
confidence: 99%
“…[15] AM techniques enable the production of geometrically complex, multimaterial medical implants with spatially heterogeneous properties that would otherwise be challenging to produce by traditional techniques. [16][17][18][19] A major AM technique utilized is extrusion-based processes to produce filaments due to the versatility and simplicity of the technique which enables a variety of materials to be processed, the ability to print in a cell-friendly Additive Manufacturing 3D printing techniques are utilized to produce biomaterial scaffolds with porous architectures that enable cell attachment, biological factors, and appropriate mechanical strength. As the basic building block of a scaffold, the individual filaments should have sufficient mechanical properties, comprising high compressive loading, and fracture resistance to mimic the natural tissue organisation.…”
Section: Doi: 101002/mame201800173mentioning
confidence: 99%
“…Computational models of degradation and bone tissue growth could be also used to predict the mechanical performance of biodegradable metals. 52 Moreover, no information is available yet concerning the fatigue behavior of these biomaterials. Given the fact that both topological design and material category significantly affect both the static and dynamic mechanical behaviors of AM porous metallic biomaterials, [53][54][55][56] there is a need for a thorough study on the dynamic mechanical responses of these porous structures.…”
Section: Mechanical Behaviormentioning
confidence: 99%
“…In this systematic search, a total of 169 porous scaffolds were identified as a rationally designed and fabricated for bone implant applications. It was found that there are three preferred strategies for fabricating bio-metamaterials: beam-based, sheet-based, and including irregular porous structures [172].…”
Section: Bone Mechanical Propertiesmentioning
confidence: 99%
“…Therefore, it is no surprising that the second most used design strategy identified in this systematic search was sheet-based representing 20.1% of the total scaffolds produced, from which all used a TPMS as unit cell. Bio-metamaterials based on TPMS can mimic the various properties of bone to an unprecedented level of multi-physics detail in terms of mechanical properties and transport properties [79,172]. Moreover, the bone-mimicking mean surface curvature of zero of TPMS eliminates the effect of stress concentrators at nodal points [120].…”
Section: Bone Mechanical Propertiesmentioning
confidence: 99%